2011
DOI: 10.1186/2047-783x-16-6-249
|View full text |Cite
|
Sign up to set email alerts
|

Comparative examination of subcutaneous tissue reaction to high molecular materials in medical use

Abstract: Polypropylene (PP), Polyethylene (PE) and polytetra-fluoroethylene (FE) are high molecular materials in medical use. They are also used as the negative control materials for ISO 10993-6 international standard biological evaluation of medical devices. We examined tissue reactions to these materials embedded subcutaneously in the dorsal area of male ddY mice. One week and 12 weeks after embedding, the tissue surrounding the embeddingg site was removed and then histopathological examination was performed. Our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 10 publications
(8 reference statements)
1
12
0
2
Order By: Relevance
“…Occasional foreign body reactions have been reported and were described as being dependent upon the amount of material introduced. 2 In a recent study with rat models, Tomida et al 3 showed that the subcutaneous introduction of polypropylene does not produce pronounced foreign body reactions. In this context, it should also be noted that polypropylene sutures are used as a negative control in the evaluation of local reactions to implanted medical products in accordance with ISO 10993-6.…”
Section: Editormentioning
confidence: 99%
See 2 more Smart Citations
“…Occasional foreign body reactions have been reported and were described as being dependent upon the amount of material introduced. 2 In a recent study with rat models, Tomida et al 3 showed that the subcutaneous introduction of polypropylene does not produce pronounced foreign body reactions. In this context, it should also be noted that polypropylene sutures are used as a negative control in the evaluation of local reactions to implanted medical products in accordance with ISO 10993-6.…”
Section: Editormentioning
confidence: 99%
“…In this context, it should also be noted that polypropylene sutures are used as a negative control in the evaluation of local reactions to implanted medical products in accordance with ISO 10993-6. 3 The absence of clinically relevant foreign body reactions might be due to the repeated removal of the SNAP suture material during each procedure. However, a non-absorbable suture should only be used for the final excision when polypropylene sutures have been well tolerated in the previous operations.…”
Section: Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Pesquisadores demonstram que há uma importante interação entre os biomateriais e o sistema imune, sendo que diferentes biomateriais induzem a graus variados de resposta imune (DING;SUN;ZHANG, 2007). A análise histológica dos tecidos adjacentes ao material implantado, durante algum tempo, foi um dos métodos mais comumente utilizados para avaliar a biocompatibilidade (TOMIDA et al, 2011). Partindo do princípio de que a biocompatibilidade é reduzida quando biomateriais induzem a expressão de maior quantidade de citocinas, essa indução pode também ser usada para analisar a intensidade de reações contra os biomateriais (HUMMEL et al, 1994;HUNT et al, 1996;DING;SUN;ZHANG, 2007).…”
Section: Mmp-13 Timp-2 Timp-3 Tnf-α E Tgf-β Durante O Processo De unclassified
“…desenvolveu um conjunto de normas embasadas cientificamente e subdivididas em 20 tópicos (ISO 10.993) para a avaliação de dispositivos e materiais de uso médico (TOMIDA et al, 2011), ainda assim o questionamento sobre o conceito de biocompatibilidade aplicado rotineiramente ao estudo de biomateriais pode ser considerado incompleto do ponto de vista imunológico, uma vez que os estudos analisam geralmente implantações únicas de tais materiais.…”
Section: Mesmo Sabendo Que a Iso (International Organization For Stanunclassified